Capitalization and Commercialization of Accreditation in the Higher Education Services Industry - Firdaus Firdaus; Ferry Fathurokhman; Zulkarnain Ridlwan; Abdul Rahman Abdul Latip; Muh Farhan Arfandy (Administrative and Environtmental Law Review, 2026)
This article critically examines the capitalization and commercialization of higher education accreditation in Indonesia. It argues that the transfer of accreditation responsibilities to Independent Accreditation Agencies (LAMs) has shifted quality assurance from a constitutional public function toward a market-oriented model. Using normative legal research with a comparative approach, the study analyzes the implications of Law No. 20 of 2003 and Law No. 12 of 2012 for the state's constitutional responsibility to guarantee the right to education. It finds that the current regulatory framework weakens state accountability and increases the financial burden on higher education institutions through accreditation fees, costs that may ultimately be passed on to students, thereby limiting equitable access to quality education. This approach contrasts with the accreditation systems in Malaysia, Thailand, Vietnam, and Singapore, where quality assurance is primarily funded by the state as a public responsibility. The article concludes that Indonesia should restore accreditation as a transparent, non-profit, and publicly financed quality assurance mechanism to strengthen the state's constitutional obligation to provide equitable and accessible higher education.